Persepsi dan Faktor-Faktor Sosial Ekonomi yang Mempengaruhi Keputusan Tenaga Kerja Lepas (BHL) Bekerja pada Perkebunan Kelapa Sawit - Nafiah, Riska Ilma; Suswatiningsih, Tri Endar; Kurniawati, Fitri (AGRIFITIA : Journal of Agribusiness Plantation, 2023)
This research conducted at PT. Nusamas Griya Lestari aims to determine the perception of casual workers (BHL) regarding the choice of working on oil palm plantations, and find out what socio-economic factors influence the length of time casual workers work on oil palm plantations. This research was conducted using a descriptive method with a quantitative approach. Sampling used a simple random sampling method with a sample size of 66 respondents. Data were analyzed using multiple linear regression analysis. The research results showed that casual workers chose to continue working on oil palm plantations because of the perception that wages were high, there were free health facilities in the form of clinics and the distance from home to the plantation were reasons for continuing to work on oil palm plantations. Based on the results of multiple linear regression analysis, age, gender and facilities provided by the company have a significant effect on the length of work of casual daily employees working on oil palm plantations.